Penguatan Kapasitas Kelembagaan Sekolah Kerja Nyata (SKN) Pesantren Darussalam Puncak Dengan Metode Aset Based Community Development (ABCD) - Ginanjar Prastyanto (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2026)
This article is the result of my community service at the Darussalam Puncak Islamic Boarding School, under the guidance of Kyai Malik. In this community service, I attempted to provide mentoring to the Real Work School (SKN), a social institution that provides entrepreneurship education to the boarding school's students. The goal of this mentoring was to strengthen the institutional governance of the SKN, which was not yet well-organized and stable, resulting in many of its programs being unsustainable. Initially, I planned to use the ABCD method in this mentoring. However, after delving into the social reality of the group I was mentoring, I felt that the ABCD method was not entirely suitable for this community, due to the unequal social relations between them, particularly between Kyai Malik and his students. Therefore, in this mentoring, I synthesized the ABCD method with a developmentalist perspective. While my mentoring is not yet complete, it has already resulted in quite positive changes. Currently, the institutional governance of the SKN is starting to be well-organized. The National Science and Technology Education (SKN) now has a well-structured entrepreneurship curriculum, consisting of two main learning activities: practice-based entrepreneurship learning and counseling-based learning.